The importance of pre-school education and the necessity of compulsory kindergarten within school stages - Hourani, Najat Abed Salem (Journal of Educational and Psychological Sciences, 2022)
The study aimed to demonstrate the importance of the first age stage of a child's life, which is the pre-school stage, and to indicate the importance of the skills that the child acquires in the pre-school education period through the kindergarten stage, and the impact of education in this period on the child's scientific future in terms of academic achievement and in terms of His personality in general, and the researcher followed the descriptive analytical approach in order to reach an answer to the study's questions and problems, and to come up with scientific results and recommendations that serve the study.The study found a set of results, including: that the pre-school education stage and the kindergarten stage have a clear and positive impact on the child’s behavior and his educational attainment. However, despite this importance, this stage is still optional in school education, and the study recommended working on selecting educational materials in the pre-school and kindergarten stages with great care that suits the requirements of children due to the seriousness of the stage, and working to prepare schools to make the kindergarten stage The educational system is a compulsory and essential stage.
Keywords: child; developmental stage; Kindergarten; pre-school education